Independent Medical Evaluation A Practical Guide - Martin, Douglas W. (Springer International Publishing, 2018)
This comprehensive book thoroughly addresses every aspect of Independent Medical Evaluations, an important part of many medical specialty disciplines where forensic opinions are needed by patients, physicians, insurers, and attorneys. Independent Medical Evaluation: A Practical Guide begins by defining the IME product and the IME evaluator themselves, explaining the medicolegal systems, and providing guidance towards establishing these professional services. Following this, the book describes how to best use medical records, and best-practices for taking an IME history and conducting an examination. The final few chapters cover developing an IME report, the common challenges and pitfalls encountered, with strategies and pearls shared to illustrate how to avoid them. Structured in a concise, practical format, this essential guide includes a large selection of sample models and templates, for additional teaching purposes. The first of its kind, Independent Medical Evaluation: A Practical Guide is a unique and ideal reference text for any physician working with IME's, from the physician conducting their first exam, to the experienced physician alike.